Identity-Forming Discourses: A Critical Discourse Analysis on Policy Making Processes Concerning English Language Teaching in Colombia - Escobar Alméciga Wilder Yesid (Universidad Nacional de Colombia, 2013)
This article addresses a critical problem about asymmetrical power relationships and uneven conditions in English language education exerted via identity shaping discourses in the document Educación: Visión 2019 issued by the Colombian Ministry of National Education. The study follows the critical discourse analysis method. It characterizes discursive strategies which, in turn, unveil power structures, means of control, and subject positioning of submission and dominance inherent in three main categories: Being bilingual, being successful, and being Colombian. It concludes that discourses are being strategically employed by the Colombian Ministry of National Education to change or preserve ideologies and to widen gaps between socio-economic groups to protect the interests of only a small segment of the population. Este reporte postula una problemática de relaciones desequilibradas de dominio, poder, control y de la desproporcionada distribución de recursos en la enseñanza del inglés en Colombia, lo cual es perpetrado por discursos que moldean la identidad, en el documento Educación: Visión 2019 publicado por el Ministerio de Educación Nacional de Colombia. El estudio sigue los principios del análisis crítico del discurso. Esta investigación caracteriza estrategias discursivas que a su vez develan estructuras de poder, medios de control, y posicionamiento de sumisión y dominio en tres categorías: ser bilingüe, ser exitoso y ser colombiano. El estudio sugiere que el Ministerio de Educación Nacional está empleando discursos para manipular ideologías y generar inequidad entre grupos sociales en tanto que protege los intereses de un segmento de la población exclusivamente.